Acute myeloid leukemia: a retrospective claims analysis of resource utilization and expenditures for newly diagnosed patients from first-line induction to remission and relapse. (4th March 2017) - Irish, William; Ryan, Michael; Gache, Larry; Gunnarsson, Candace; Bell, Timothy; Shapiro, Mark
Abstract: Objective: The objective of this study was to estimate resource utilization and expenditures for patients with acute myeloid leukemia (AML) in a real-world claims database. Research design and methods: AML patients were identified in MarketScan claims databases between 1 January 2009 and 31 January 2015. Patients had a minimum of two AML diagnosis codes, hospitalization within 14 days after initial diagnosis, and ≥6 months of enrollment before initial diagnosis. Patients were monitored from first-line induction to a record of remission. A subset had a record of a second treatment period, defined as time from relapse to remission. Patient demographics, AML risk factors, and comorbidities were recorded. Descriptive analysis of utilization and expenditures (in 2014 $US) were reported for each cohort. Results: The inclusion criteria were met in 1597 patients (mean age, 58.4 years; 51.0% male). Ninety percent of patients had ≥1 risk factor for AML. Mean (SD) healthcare expenditures for patients from first-line induction to remission ( n  = 681) were $208, 857 ($152, 090). Of the 157 who had a record of relapse, 70 had a record of a second remission. Expenditures for these patients ( n  = 70) from relapse to remission were $142, 569 ($208, 307); 60% were admitted to a hospital for a mean of 18.5 hospital days, and 20% had ≥1 emergency room visit. Conclusions: Although this claims-based analysis is limited by a lack of generalizability to noninsured populations and potential underreporting of certain events and diagnoses, we found that treating AML patients poses a significant healthcare burden, during both first-line induction and relapse. With people living longer, the number of cases of AML is expected to increase in the future.